Equilibrium Study of Protein Denaturation by Urea - Canchi, Deepak R; Paschek, Dietmar; García, Angel E (Journal of the American Chemical Society, 2010)
Though urea is commonly used to denature proteins, the molecular mechanism of its denaturing ability is still a subject of considerable debate. Previous molecular dynamics simulation studies have sought to elucidate the mechanism of urea denaturation by focusing on the pathway of denaturation rather than examining the effect of urea on the folding/unfolding equilibrium, which is commonly measured in experiment. Here we report the reversible folding/unfolding equilibrium of Trp-cage miniprotein in the presence of urea, over a broad range of urea concentrations, using all-atom Replica exchange MD simulations. The simulations capture the experimentally observed linear dependence of unfolding free energy on urea concentration. We find that the denaturation is driven by favorable direct interaction of urea with the protein through both electrostatic and van der Waals forces and quantify their contribution. Though the magnitude of direct electrostatic interaction of urea is larger than van der Waals, the difference between unfolded and folded ensembles is dominated by the van der Waals interaction. We also find that hydrogen bonding of urea to the peptide backbone does not play a dominant role in denaturation. The unfolded ensemble sampled depends on urea concentration, with greater urea concentration favoring conformations with greater solvent exposure. The m-value is predicted to increase with temperature and more strongly so with pressure.